Transcatheter closure of tubular PDA with amplatzer plug 4 in preterm infants weighing between 900 and 3,400 g: the pros and cons - Mini, Nathalie; Schneider, Martin B. E.; Schneider, Katja (Frontiers in Cardiovascular Medicine, 2023)
Objective To our knowledge, no prior study has focused on the outcome of PDA occlusion using an Amplatzer™ Vascular Plug 4 (AP4) in ill preterm infants. This study aims to highlight the pros and cons of AP4 in this cohort. Methods Between 2020 and 2022, 26 ill preterm infants underwent PDA closure in our centre. The median age, weight, and gestational age were 60 days (11–180 days), 1,900g (900–3,400 g), and 25 weeks (22–33 weeks), respectively. The indication of the intervention was hemodynamically significant PDA. A medical trial with non-steroid medication failed to close the ducts in all patients. Follow-up using echocardiography was done 24, 48, and 72 h after the intervention. Results Of 26 ducts, 21 were successfully closed with AP4. Five ducts shorter than 7 mm were unsuitable for AP4 and were closed with the Amplatzer Piccolo device. The median radiation time was 4 min (3–9 min). No early plug-related complications or deaths were documented. Plug-related jailing of the left pulmonary artery as a late complication was 9.5%, and LPA reintervention was required. All ducts were closed after 48 h. Conclusion Implantation of the AP4 using a 4 F 0.38 guide wire-compatible catheter without inserting a long sheath makes the closure of tubular ducts with this device feasible and uncomplicated with a short intervention time. However, the limited sizes with fixed lengths of the AP4 make it unsuitable for ducts wider than 4.5 mm and shorter than the chosen device length, which can increase the risk of significant left pulmonary stenosis. A wide range of plug diameters and lengths is required to accommodate the large and short ducts.